Pledges of commitment and cooperation in partnerships - Lachlan Deer; Ralph-C. Bayer (University of Zurich, Department of Economics, 2015)
We use experimental methods to investigate whether pledges of commitment can improve cooperation in endogenously formed partnerships facing a social dilemma. Treatments vary in terms of the individual's (a) opportunity to commit to their partner, (b) the cost of dissolving committed partnerships, and (c) the distribution of these dissolution costs between partners. Our findings show that pledges of commitment increase cooperation in committed partnerships when costs to dissolve them are shared equally among partners. In contrast, when costs to dissolve committed partnerships fall solely on the individual choosing to break up, pledges of commitment fail to improve cooperation and instead decrease cooperation.
Keywords: C92; D03; D83; H41; 330; Commitment; Cooperation; Endogenous Group Formation; Experiment